(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
At present stage due to modern lifestyle, nuclear family and working motherhood, the rest needed for the women during menses time and during and after delivery have been reduced. Protrusion of the pelvic organs into or out of the vaginal canal is termed as Pelvic organ prolapse. It is also called pelvic relaxation. It results from weakening or damage to pelvic supporting structures, which can occur generally throughout the vagina or at specific sites. This problem may develop after child birth, progression of age, and injury to the muscles and organs situated there. Anything that causes increased pressure in the abdomen can lead to pelvic organ prolapse. Some common causes include: pregnancy, labour, and childbirth (the most common cause) etc. Acarya Susrutha mentions that in Prasramsini, any irritation causes excessive vaginal discharge/displacement and labour is difficult/abnormal. Dalhana explains the reason for difficult labour is abnormality in passage. Clinical features of Pitta vitiation i.e., burning sensation and heat etc. are present. According to WHO estimation, the global prevalence of uterine prolapse is 2- 20%. As Prasramsini is a Pittaja yoni vyapat and Vata is the main Dosa involved in all the Yoni vyapat, the drug selected for the study is mainly Vata pitta hara and Balya. Hence an attempt was made by giving tablet Neo (Charak pharmaceuticals) orally, and Mahamasha tailam for Abyangam and Yoni pichu dharana.